Quantum Spin Dynamics of Individual Neutral Impurities Coupled to a Bose-Einstein Condensate - Schmidt, Felix; Mayer, Daniel; Bouton, Quentin; Adam, Daniel; Lausch, Tobias; Spethmann, Nicolas; Widera, Artur (Physical Review Letters, 2018)
We report on spin dynamics of individual, localized neutral impurities immersed in a Bose-Einstein condensate. Single cesium atoms are transported into a cloud of rubidium atoms and thermalize with the bath, and the ensuing spin exchange between localized impurities with quasispin Fi=3 and bath atoms with Fb=1 is resolved. Comparing our data to numerical simulations of spin dynamics, we find that, for gas densities in the Bose-Einstein condensate regime, the dynamics is dominated by the condensed fraction of the cloud. We spatially resolve the density overlap of impurities and gas by the spin population of impurities. Finally, we trace the coherence of impurities prepared in a coherent superposition of internal states when coupled to a gas of different densities. For our choice of states, we show that, despite high bath densities and, thus, fast thermalization rates, the impurity coherence is not affected by the bath, realizing a regime of sympathetic cooling while maintaining internal state coherence. Our work paves the way toward the nondestructive probing of quantum many-body systems via localized impurities.
CRIS-Team Scopus Importer:2023-03-27